Maternal Reason for Choosing Caesarean Section at Won Request and Without Medical Indication : A Literature Review - Cipta Wardhani, Gusna Pricilia; Pudji Lestari (Journal of Community Medicine and Public Health Research, 2024)
New research from the World Health Organization (WHO) shows that the incidence of caesarean sections in childbirth continues to increase globally, accounting for more than 1 in 5 (21%) of all births. Although there is a considerable amount of literature on complications following caesarean section, the demand for caesarean section without medical indication and at maternal request is increasing. This study aimed to identify the reasons why mothers choose to have a caesarean section without a medical indication. Mothers may choose to have a caesarean section due to fear of vaginal delivery, concerns about perceived health risks, previous traumatic childbirth experiences, worries about future sexual life, positive attitudes towards the caesarean section, and the decision-making process. It can be concluded that many expectant mothers are not adequately prepared for this process. Tackling this problem requires collaboration between different stakeholders. WHO has recommended guidelines for non-clinical interventions to reduce unnecessary caesarean sections, targeting women, health professionals and health organizations, facilities, or systems.